Phoneme-Based English-Yorùbá Machine Transliteration - Asahiah, Franklin; Akioyamen, Victor Isebaga (Ife Journal of Technology, 2024)
One of the challenges for translating English to Yorùbá in Nigeria is the foreign names and technical terms in news articles and scientific documents. Much of names and terms contain letters not used in Yorùbá language. We present a rule-based model for the transliteration of English noun words to Yorùbá such that the output respects the morphology and phonology of the target language. The model which is phoneme-based, relied upon the CMU pronouncing dictionary to get the phoneme for each word. At the implementation of the model, test carried out on standardized words of 55 words yielded an accuracy of 72.7%, recall of 0.98, precision of 0.965 and F score of 0.972. A second test of non-standardized set references has accuracy of 40.7%, recall of 0.91, precision of 0.925 and F score of 0.912. A few challenges identified with the model include inability to correctly render some of the vowels as required by the phonology of the target language.